The Investigation Process Prevention And Eradication Of Narcotics Investigator To The Criminal Abuses By Police - Ali Murtadho (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
Narcotics abuse is a transnational crime that is done by using a high modus operandi, advanced technology, and supported by jarigan organized. Narcotics are also considered an extraordinary crime because of the impact and the dangers posed to health damage as well as disorders of the nervous system of human, narcotics on one side are the drugs or substances that are useful in the field of medicine and the development of science and on the other hand can cause dependence highly detrimental if abused. Therefore, it is necessary to prevent and fight against the crime of abuse in the illicit traffic of Narcotics. Given the extraordinary crime then categorized the crime of Narcotics regulated more specifically in the Narcotics Act No. 35 of 2009 on Narcotics. In the prevention and eradication of Narcotics Police have an important role in it. In addition to enforcing the law, the police are also expected to minimize the prevention and guidance prior to the crime of Narcotics. As a form of law enforcement committed the offenses Police Narcotics abuse is to take action in the form of an investigation. Intent and purpose of the investigation is done to make light of a criminal offense to known suspects and to provide legal certainty and a sense of justice to citizens.Keywords: Process; Investigation; Eradication; Narcotics; Police.